Telehealth: Could It Be an Avenue to Microvascular Breast Reconstruction for Patients with Geographical Barriers? - Colakoglu, Salih; Johnson, Ariel; Mureau, Marc A.M.; Douglass, Sara; Kaoutzanis, Christodoulos; Chong, Tae W.; Mathes, David W.; Cohen, Justin B. (Journal of Reconstructive Microsurgery, 2021)
Background All women undergoing a mastectomy have the right to reconstruction. However, many women do not receive reconstruction and many more are not aware of all the reconstructive options available to them. Travel distance to a center that provides reconstruction and subsequent follow-up may be a contributing factor to this disparity especially among those who seek microsurgical options. Telehealth, which provides patients with remote video consultations and decreases the travel burden, may be a solution to optimize the accessibility of breast reconstruction for these patients. The purpose of this study was to discuss the efficacy and reliability of telehealth to overcome geographic barriers.Methods Patients who received breast reconstruction and participated in video telehealth visits between February and May 2020 were included in this study. Patient demographics, comorbidities, and clinical outcomes were collected. Video telehealth encounters were reviewed to determine specific concerns and questions discussed during these encounters.Results A total of 235 breast reconstruction surgery patient encounters were recorded for 4 plastic surgeons who offer microsurgical breast reconstruction. Eighty-eight patients (37.4%) were seen as telehealth visits, 20 (22.7%) of which were new patient visits. Eight (9.09%) patients were microsurgical breast reconstruction candidates and 25 (28.4%) were following-up after microsurgical breast reconstruction. The majority of telehealth visits included normally healing wounds in the postoperative patient.Conclusion Telehealth provides an avenue for premastectomy consultation, second opinion visits, and postoperative follow-up for patients who have geographical barriers precluding them from reaching plastic surgeons who perform all types of breast reconstruction.
Keywords: breast reconstruction; perforator flap; microsurgery; telehealth; telemedicine